Cybercrime is Very Dangerous Form of Criminal Behavior and Cybersecurity - Siniša Franjić (Emerging Science Journal, 2020)
Computer crime is a form of criminal behavior in which the use of computer technology and information systems is manifested as a mode of crime or the computer is used as a means or purpose of perpetration with which is producing some relevant criminal consequence. Computer crime is also an unlawful violation of property in which computer data is intentionally altered (manipulated by a computer), destroyed (computer sabotaged) or used in conjunction with hardware (theft of time). Objective of this paper is consideration of using new computer technology in everyday life. Unfortunately, some users using new technology for criminal acts. For Analysis, author use official resources from books, scientific papers and online resources. Even though it is a new technology, police and justice successfully deal with different types of computercrimes.